REARING OF EARLY JUVENILES OF SPINY LOBSTER PANULIRUS VERSICOLOR (LATREILLE) WITH NOTES ON LOBSTER FISHERY IN VIZHINJAM AREA - Kuthalingam, M D; Luther, G; Lazarus, S (Indian Journal of Fisheries, 2011)
Juveinles of the spiny lobster Panulirus versicolor mersuring in carapacelength from 9 mm to 21 mm, collected from the crevices of rocks inside the breakwaterarea in theVizhinjam Bay at a depth of about 6 meters were reared in the ;laboratory glass tanks. The results revealed an increment of growth of 1.82 mmto 3.58 mm in carapace length with an average at 2.84 mm per month. The lobsterfishery at Vizhinjam area together with prioe index is outlined.